The Effect of Infrastructure and Logistics Performance on Economic Performance: The Mediation Role of International Trade. Issue 4 (November 2020) - Yeo, Alassane D.; Deng, Aimin; Nadiedjoa, Todine Y.
This paper evaluates the effect of infrastructure and logistics performance on economic performance. In addition, the mediating role of international trade on the relationship between infrastructure and economic performance, and logistics performance and economic performance, respectively. Generalized Structured Component Analysis (GSCA) was proposed as a Component-Based Approach to Structural Equation Modeling (SEM) to test several hypotheses regarding the interaction of the latent variable. Furthermore, the mediation analysis using regression was performed. Based on data from middle income selected countries, the hypothesis about the mediation role of international trade was partially supported. Our results also suggest that infrastructure and logistics performance improvements may enhance middle-income countries sustainable growth with increasing international trade volume. JEL: F43, L90, P33